Power of Articulation Imagery of Social Structure and Social Change - Kortesoja, Matti (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
"The book's original contribution to contemporary conceptual history - particularly in the field of political and sociological intellectual histories - consists of mapping of the concept of articulation as an Ariadne's thread that can shed light on conceptualisations of society and their shifts. As the author of the book rightly emphasizes, the metaphors that theorists use to describe society are not only words but concrete attempts to grasp the social as well as normative approaches that indicate how to best organize it. That is, societal metaphors are not neutral. The topic is of enormous importance for sociological and political analysts in particular". - Dr Sara R. Farris, Associate Professor, Department of Sociology, Goldsmiths College, University of London This open access book is the first book that attempts to treat the notion of articulation as an important concept to be added to the lexicon of communication studies and social science. It constitutes the first comprehensive and systematic discussion of 'articulation' in English, providing an introduction of its usages and what has occurred on its 'travels' from one theoretical realm to another in political philosophy, structural linguistics, new economic anthropology, cultural studies and post-Marxist discourse theory. The proposed research takes a relational approach to society and social action in a way that recognises their relative autonomy. It entails an introduction of the 'discursive turn' in the imagery of society and social change, thereby proving that the relational concept of articulation/Gliederung has potential to consider society as both a structured, complex whole and a product of human interaction. Matti Kortesoja is a Postdoctoral Researcher at the Tampere Research Centre for Journalism, Media and Communication (COMET), Tampere University, Finland.